(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The Hănțilă method has proven its effectiveness in solving three-phase circuits with nonlinear elements and presents several advantages compared to other methods. It is a fixed point method and the solution is obtained by constructing a Picard-Banach sequence with assured convergence. Sometimes the contraction factor of the sequence construction operator is very close to 1 and thus convergence is slow. To develop the method and increase its efficiency, we propose and analyze several procedures to accelerate the calculation algorithm.